Why are consumers following social media influencers on Instagram? Exploration of consumers' motives for following influencers and the role of materialism. Issue 1 (2nd January 2022) - Lee, Jung Ah; Sudarshan, Sabitha; Sussman, Kristen L.; Bright, Laura F.; Eastin, Matthew S.
Abstract: Despite the ubiquity of social media influencers (SMIs) and the clear value they hold for marketers, little is understood about the sociopsychological motives that drive consumers to follow them. The current research identified unique consumer motivations for following SMIs on Instagram and examined its association with important consumer behaviour outcomes (i.e. trust towards SMIs' brand-related posts and frequency of purchasing SMI-recommended brands) as well as materialism. Based on survey data, findings revealed four motivations for following influencers on Instagram – authenticity, consumerism, creative inspiration, and envy – which had varying effects on trust and purchase frequency. Additionally, materialism was a significant individual difference variable that was strongly associated with the four motives, some of which served as key mediators underlying materialism's impact on purchase behaviour. Managerial and theoretical implications for marketers and advertisers are discussed as well as suggestions for future research in this burgeoning area.